2009
DOI: 10.1007/s11738-009-0271-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV-B radiation on the growth and antioxidant enzymes of Antarctic sea ice microalgae Chlamydomonas sp. ICE-L

Abstract: The effect of ultraviolet-B (UV-B) radiation on Antarctic phytoplankton has become an attractive ecological issue as a result of annual springtime ozone depletion. The effects of UV-B radiation on the growth and antioxidant enzymes were investigated using Antarctic sea ice microalgae Chlamydomonas sp. ICE-L as the material in this study. The results demonstrated that UV-B radiation could notably inhibit the growth, especially at high UV-B radiation intensity (70 lW cm -2 ). Malondialdehyde and O 2 Á-content in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The assay for total SOD (EC1.15.1.1) activity was based on the method according to Wang et al (2009). One unit of SOD activity is defined as the amount of enzyme required to inhibit the reduction of nitroblue tetrazolium (NBT) by 50%.…”
Section: Antioxidant Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…The assay for total SOD (EC1.15.1.1) activity was based on the method according to Wang et al (2009). One unit of SOD activity is defined as the amount of enzyme required to inhibit the reduction of nitroblue tetrazolium (NBT) by 50%.…”
Section: Antioxidant Enzymesmentioning
confidence: 99%
“…6) (Asada 2006;Gong et al 2006). SOD is considered to constitute the first line of defense against ROS, which catalyzes superoxide radical (O 2 Á-) to O 2 and H 2 O 2 which are further scavenged by various antioxidant enzymes (Demiral and Turkan 2005;Wang et al 2009;Zhang et al 2004;Asada 2006), the most important being CAT and POD (Gong et al 2006). Reports have shown that CAT is critical and indispensable for maintaining the redox balance during oxidative stress (Willekens et al 1997).…”
Section: Defensive Mechanismmentioning
confidence: 99%
“…Meanwhile, changes in morphology to increase shelf-shading were regarded as the other effective trait (Wu et al, 2005). In addition, microalgae activated antioxidant system against oxidative stress or screened damaging UVR by UV-absorbing compounds (Wang et al, 2009). When damage of DNA and protein occurs, the repair and resynthesis of sensitive targets in the microalgae become important (Coesel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The Cyt c method has been used in vitro to measure O 2 • from PSII-enriched membrane fragments from higher plants [263], from apoplasts of wheat roots [314] and from Chlamydomonas sp. ICE-L suspension [264]. In addition to O 2 • , Cyt c can be reduced by the components of the photosynthetic electron transport chain [315,316] and by ascorbate, GSH and other reductants [317].…”
Section: Dyes Nbt Nbd and Xtt Nitro Blue Tetrazolium (Nbt) Is A Tramentioning
confidence: 99%
“…For this reason, comparison of the results obtained with and without added SOD is always required [263]. To enhance the specificity of Cyt c to O 2 • , it is possible to use acetylated Cyt c [318], for example with Chlamydomonas in [264]. However, reduced Cyt c can also be reoxidized by many cell components, like cytochrome oxidases and peroxidases and by oxidants like peroxynitrite (ONOO -) [317], which calls for care with the use of the method.…”
Section: Dyes Nbt Nbd and Xtt Nitro Blue Tetrazolium (Nbt) Is A Tramentioning
confidence: 99%